PEMBUATAN VIDEO PEMBELAJARAN PROSEDUR PEMELIHARAAN PERALATAN TATA UDARA RUANG TINGGAL (ROOM AIR CONDITIONER/ RAC) - Imam Arif Raharjo; Sri Sujanti; Bambang DK (Fakultas Teknik Universitas Negeri Jakarta, 2017)
Making Video Learning of Maintenance Procedure for Air Conditioning Equipment (Room Air Conditioner / RAC). This innovative work aims to make a learning video about the procedure for maintaining air space equipment (RAC) which can later be used as one of the variations in teacher learning media in the learning process. Making this innovative work uses a strategy and manufacturing procedure with three stages, namely planning, recording, and production. Responses were made by respondents consisting of a Media Expert and Vocational High School students using opinion instruments. The conclusion of the making of this innovative work is that a learning video is produced about the procedures for maintaining air-conditioning equipment (Room Air Conditioner / RAC). Abstrak Pembuatan Video Pembelajaran Prosedur Pemeliharaan Peralatan Tata Udara Ruang Tinggal (Room Air Conditioner/ RAC). Karya Inovatif ini bertujuan untuk membuat video pembelajaran tentang prosedur pemeliharaan peralatan tata udara ruang tinggal (Room Air Conditioner/ RAC) yang nantinya dapat digunakan sebagai salah satu variasi media pembelajaran guru dalam proses pembelajaran. Pembuatan karya inovatif ini menggunakan strategi dan prosedur pembuatan dengan tiga tahapan yaitu perencanaan, perekaman, dan produksi. Tanggapan dilakukan oleh responden yang terdiri dari seorang Ahli Media dan siswa Sekolah Menengah Kejuruan dengan menggunakan instrument opini. Kesimpulan dari pembuatan karya inovatif ini adalah dihasilkan sebuah video pembelajaran tentang prosedur pemeliharaan peralatan tata udara ruang tinggal (Room Air Conditioner/ RAC) .